Sir Cumference and the Isle of Immeter : a math adventure - Neuschwander, Cindy; Geehan, Wayne (Watertown, MA : Charlesbridge, 2006)
Discusses young Per taking a mathmatical adventure.
Keywords: Geometry -- Juvenile literature; Geometry